KEMAMPUAN LITERASI INFORMASI MAHASISWA JURUSAN FISIKA UIN MALANG DALAM MENGERJAKAN TUGAS MAKALAH MATKUL ELEKTRONIKA - Rizkyah, Inez Fahira; Rifana, Wulan Wahyu (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2023)
This study aims to analyze using the seven pillars theory in interviews with students while working on class assignments. The seven pillars theory is a framework used to develop information literacy skills. Qualitative research methods use in-depth interviews as a data collection instrument. Interviews were conducted to understand how students use the Seven Pillars theory steps in collecting, evaluating, and using information when doing their coursework. The study results show that students tend to understand the Seven pillars theory steps well. They recognize the importance of identifying information needs, finding relevant sources, and selecting the most essential information for their task. However, most students face difficulties evaluating the reliability and sustainability of the information they find. In terms of information, students tend to use the information they see in their assignments. However, there were some challenges, such as difficulties in synthesizing and integrating disparate information into their task framework. This study's findings indicate that using the Seven Pillars theory in interviewing students while doing coursework can help them develop better information literacy skills. This study recommends improving teaching and learning approaches in tertiary institutions by emphasizing the use of the Seven Pillars theory in developing students' information literacy skills.